Accelerometer in Epley Manoeuvre Treatment for Benign Paroxysmal Positional Vertigo using Arduino Pro-Mini 328 - Kholid, Mohd Khairilnazmi; Baharudin, Elfarizanis (Evolution in Electrical and Electronic Engineering, 2021)
Benign Paroxysmal Positional Vertigo (BPPV) is a spinning sensation as if the space or surrounding environment is spinning in circles around the person. Some techniques include using photos and videos to help individuals through the procedure, but it is also necessary to overcome the uncertainty that comes with shifting the head from a specific position. This movement tracking was built around an Arduino microcontroller for rapid development and prototyping. The microcontroller performs three important tasks: position computations based on inertial measurement unit (IMU) data, instructing the user on how to adjust their body, and ensuring that motions are executed correctly. This project may enable a doctor or a patient to easily cure BPPV. Doctors are unable to treat BPPV patients with medication since the illness is similar to a headache. The Epley Manoeuvre is a therapy for BPPV that might gradually decrease the condition. Most patients are relieved that their condition may be quickly resolved with the help of a health care practitioner who is well-versed in the diagnosis and treatment of BPPV, allowing their world to stop spinning. This project can make a significant improvement using the technology that is now being developed at the forefront of innovation, and it will be practical and, hopefully, result in a decent product.